2020
DOI: 10.1038/s41380-020-00881-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in network centrality of psychopathology symptoms between the COVID-19 outbreak and after peak

Abstract: The current study investigated the mechanism and changes in psychopathology symptoms throughout the COVID-19 outbreak and after peak. Two studies were conducted separately in China during outbreak and the after peak stages, with 2540 participants were recruited from February 6 to 16, 2020, and 2543 participants were recruited from April 25 to May 5, 2020. The network models were created to explore the relationship between psychopathology symptoms both within and across anxiety and depression, with anxiety meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
124
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 68 publications
30
124
3
1
Order By: Relevance
“…Our findings are consistent with those found by Wang et al (2020) in a study of depression and anxiety symptoms during the outbreak of the pandemic in China except that these authors also found restlessness, psychomotor problems and suicidality also to be central symptoms. Thus, bodily troubles and suicidality appeared to have more influence on other symptoms in China than in Norway.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with those found by Wang et al (2020) in a study of depression and anxiety symptoms during the outbreak of the pandemic in China except that these authors also found restlessness, psychomotor problems and suicidality also to be central symptoms. Thus, bodily troubles and suicidality appeared to have more influence on other symptoms in China than in Norway.…”
Section: Discussionsupporting
confidence: 93%
“…Related to COVID-19 pandemic, Wang et al (2020) investigated the MDD and GAD networks among Chinese adults during the COVID-19 outbreak and after peak. At outbreak, the MDD symptoms depressed mood, loss of energy, psychomotor problems and suicidality and the GAD symptoms generalized worry, trouble relaxing and restlessness showed high strength centrality.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the COVID-19 pandemic, only a few studies have so far applied a network analytic framework to examine the interdependence between different factors assumedly ANXIETY DURING THE COVID-19 LOCKDOWN 6 involved in the psychological responses to the pandemic, and especially regarding the fear of infection or the anxious response to the structural impact of the pandemic (e.g., Jiang et al, 2020;Papini et al, 2020;Taylor et al, 2020). And for the anxiety symptoms reported in the general population during the COVID-19 pandemic, only two studies (i.e., Hoffart et al, 2020;Wang et al, 2020) have, until now, investigated the interrelationships between the distinct hallmark symptoms of GAD as experienced during lockdown through the lens of the network approach. For ease of comparison, both studies (i.e., Hoffart et al, 2020;Wang et al, 2020) relied on the Generalized Anxiety Disorder-7 (GAD-7; Spitzer et al, 2006), one of the most commonly used self-reported screening tools in epidemiological and clinical research for assessing GAD symptoms (e.g., Schalet et al, 2014).…”
Section: Anxiety During the Covid-19 Lockdownmentioning
confidence: 99%
“…And for the anxiety symptoms reported in the general population during the COVID-19 pandemic, only two studies (i.e., Hoffart et al, 2020;Wang et al, 2020) have, until now, investigated the interrelationships between the distinct hallmark symptoms of GAD as experienced during lockdown through the lens of the network approach. For ease of comparison, both studies (i.e., Hoffart et al, 2020;Wang et al, 2020) relied on the Generalized Anxiety Disorder-7 (GAD-7; Spitzer et al, 2006), one of the most commonly used self-reported screening tools in epidemiological and clinical research for assessing GAD symptoms (e.g., Schalet et al, 2014). In their study, Wang et al (2020) identified excessive worry, trouble relaxing, and restlessness as the most central nodes in the structure of GAD symptoms among Chinese adults during the early first weeks of the outbreak (i.e., lockdown).…”
Section: Anxiety During the Covid-19 Lockdownmentioning
confidence: 99%
See 1 more Smart Citation